2012
DOI: 10.3856/vol40-issue4-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

The zooplankton of Santa Catarina continental shelf in southern Brazil with emphasis on Copepoda and Cladocera and their relationship with physical coastal processes

Abstract: ABSTRACT. Very few studies have been carried out to exclusively investigate the zooplankton community of Santa Catarina State continental shelf, despite the economic and ecological importance of the area. This coastal region of southern Brazil presents highly relevant oceanographic processes, such as the strong influence of continental inputs, resurgence in the Cabo de Santa Marta Grande and River Plata plume water to the south. Two sampling cruises were carried out, in December 2005 and May 2006, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In this case, it is important to consider the extremes groups: the most abundant, and the most variable ones. Diatomacea dominated the phytoplankton samples while Copepods (Crustacea: Maxillopoda) and cladocerans (Crustacea: Branchiopoda) dominated throughout the sampling cruises, as had occurred in other studies undertaken in Brazilian coastal waters (DOMINGOS-NUNES;RESGALLA JR., 2012;LOPES, 2007;RESGALLA JR., 2011). Copepods and cladocerans high densities in all sites and seasons suggest that these crustaceans may be an Appendix 2 cont.…”
Section: Discussionsupporting
confidence: 64%
“…In this case, it is important to consider the extremes groups: the most abundant, and the most variable ones. Diatomacea dominated the phytoplankton samples while Copepods (Crustacea: Maxillopoda) and cladocerans (Crustacea: Branchiopoda) dominated throughout the sampling cruises, as had occurred in other studies undertaken in Brazilian coastal waters (DOMINGOS-NUNES;RESGALLA JR., 2012;LOPES, 2007;RESGALLA JR., 2011). Copepods and cladocerans high densities in all sites and seasons suggest that these crustaceans may be an Appendix 2 cont.…”
Section: Discussionsupporting
confidence: 64%
“…The greater abundance of copepods in the south region was also reported by Nunes & Resgalla Jr. (2012). Cladocera was not observed in the samples of the VOR that it only operates in a narrow depth range, which is outside the preferential distribution of the group even though Resgalla Jr. & Montú (1993) and Muxagata & Montú (1999) reported in the southern coast and southeastern Brazilian.…”
Section: Discussionsupporting
confidence: 57%
“…Almost a century later, P. schmackeri was found near the Rio Una do Prelado River on the Brazilian coast (Rocha, 1985). It became established in this region and spread from Guanabara Bay to Rio Grande do Sul (Resgalla & Montú, 1993;Marazzo, 2002;Domingos-Nunes & Resgalla, 2012;Monteiro-Ribas et al, 2012). Moreover, sporadic records are reported in Aqaba Bay (Red Sea), in Madagascar (Indian Ocean) (Onbe, 1999) and in Port Tawfiq at the southern entrance to the Suez Canal (Gurney, 1927).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kim & Onbe (1989) P. schmackeri prefers warm water with low salinity; in the north-western Pacific and in the south-western Atlantic, the species was recorded in a temperature range 21-27 °C and a salinity range 19-34 (Onbe, 1983;Rocha, 1985;Onbe & Ikeda, 1995;Marazzo, 2002;Domingos-Nunes & Resgalla, 2012;Monterio Ribas et al, 2012). In the present study, it was found in summer, when temperature and salinity are higher (26.4-29.1 °C and 37.39-37.96, respectively) than those mentioned by the above authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation